Distribution of dendritic cells in the pilosebaceous unit of the scalp in subversive abscessing perifolliculitis of the scalp: immunomorphological aspects - Poslavska , O.V.; Statkevych, O.L.; Sviatenko, T.V.; Chekan , S.M. (Medicni Perspektivi, 2025)
Abscessing perifolliculitis of the scalp (Hoffmann’s disease) is a rare but serious chronic purulent-inflammatory disease of the hair follicles, which leads to the formation of deep abscesses, cicatricial alopecia and a significant decrease in the quality of life of patients. Our observations of the increase in cases allow us to state the relevance of this problem today and the need for additional, more thorough study of the pathology of the immune system underlying this pathological process. In the skin, one of the leading places among the cells that maintain local immune homeostasis and initiate protective innate and adaptive immune responses is occupied by Langerhans cells or the so-called dendritic cells of the epithelium. The aim of the work is to investigate the number and location of skin dendritic cells (separately subpopulations of Langerhans cells and dermal dendritic cells) in subacute abscessing perifolliculitis of the head, with special attention to damage to the structures of the pilosebaceous unit of the skin. Biopsy material from patients diagnosed with abscessing perifolliculitis of the head (Hoffmann’s disease) who underwent examination and treatment at the medical center of the private enterprise “Dzerkalo”, Dnipro, Ukraine, was studied. All patients were male military personnel, whose age ranged from 20 to 51 years, the average age was 35.5±11.54 years. IHC was performed according to the TermoScientific (TS) protocols with primary antibodies to dendritic cells (CD1a, RTU). The Lab Vision Quanto (TS, USA) imaging system was used with the determination of the reaction using the DAB Quanto Chromogen (TS, USA) chromogen. Studies of the number and distribution of CD1a (+) cells (epidermal Langerhans cells and dermal dendritic cells) revealed significant differences in their accumulation and branching for the comparison groups. The greatest difference was demonstrated by areas of hair follicles where Langerhans cells were absent in the control group, namely in the internal root epithelial sheath, as well as in the hair dermal papilla (all p<0.05). In comparison, in abscessing perifolliculitis of the head, CD1a (+) cells actively accumulated in these areas with spread to areas around the sebaceous glands and muscles that lift the hair, with significant infiltration of all structures of the pilosebaceous unit and the surrounding dermis or hypodermis stroma. The average number of Langerhans cells among keratinocytes in the study group significantly exceeded the control group’s indicators (26.07±11.51 cells compared to 6.02±11.51 cells, respectively (p<0.05)), and also demonstrated a wide network of branched processes. The stratified squamous epithelium in abscessing perifolliculitis of the head was characterized by acanthosis, hyperplasia, and increased mitotic activity. Accumulation of CD1a (+) cells in the internal root epithelial sheath and hair dermal papilla was observed only in the study group and was absent in the control group, (p<0.05). In the outer root epithelial sheath of pilosebaceous units around the hair follicle bud roller, the number of CD1a (+) cells in the study group significantly exceeded the control group (31.44±8.86 cells compared to 4.84±1.12 cells, respectively (p<0.05)), due to which T-lymphocyte infiltration with prolonged inflammatory damage and alopecia is probably maintained in this area. A statistically significantly higher density of infiltration by CD1a (+) dendritic cells in the area of the excretory ducts of the secretory departments of the sebaceous glands in the study group compared to the control group (17.87±11.65 cells compared to 6.24±2.05 cells, respectively (p<0.05)) due to excessive antigenic stimulation may be the cause of sebaceous gland hyperplasia. The increased density of antigen-presenting cells such as CD1a (+) dendritic cells among the inflammatory infiltrate of the dermis in PCAS compared to the control group (52.50±16.77 cells compared to 6.87±3.13 cells, respectively (p<0.05)) indicates the active migration of these motile cells and the predominance of effector mechanisms of the immune response around the pilosebaceous units of the scalp.